Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine which systems of equations have no solution, we will analyze each system step by step to check for consistency. A system of linear equations has no solution if the equations describe parallel lines that never intersect.
### System 1
[tex]\[ \begin{aligned} x + 4y &= 23 \quad \text{(1)} \\ -3x &= 12y + 1 \quad \text{(2)} \end{aligned} \][/tex]
First, rewrite equation (2) to make it similar to equation (1):
[tex]\[ -3x - 12y = 1 \][/tex]
Now, let's put both equations in standard form:
[tex]\[ \begin{aligned} x + 4y &= 23 \\ -3x - 12y &= 1 \end{aligned} \][/tex]
Multiply equation (1) by 3:
[tex]\[ 3(x + 4y) = 3 \cdot 23 \implies 3x + 12y = 69 \][/tex]
Now we have:
[tex]\[ \begin{aligned} 3x + 12y &= 69 \\ -3x - 12y &= 1 \end{aligned} \][/tex]
Add these two equations:
[tex]\[ (3x - 3x) + (12y - 12y) = 69 + 1 \implies 0 = 70 \][/tex]
This is a contradiction. Therefore, System 1 has no solution.
### System 2
[tex]\[ \begin{aligned} 2x + 4y &= 22 \quad \text{(1)} \\ -x &= 2y - 11 \quad \text{(2)} \end{aligned} \][/tex]
Rewrite equation (2) to standard form:
[tex]\[ -x - 2y = -11 \][/tex]
Now, put the equations together:
[tex]\[ \begin{aligned} 2x + 4y &= 22 \\ -x - 2y = -11 \end{aligned} \][/tex]
Multiply equation (2) by 2:
[tex]\[ -2x - 4y = -22 \][/tex]
Now we have:
[tex]\[ \begin{aligned} 2x + 4y &= 22 \\ -2x - 4y &= -22 \end{aligned} \][/tex]
Add these two equations:
[tex]\[ (2x - 2x) + (4y - 4y) = 22 - 22 \implies 0 = 0 \][/tex]
This is an identity, meaning the system has infinitely many solutions. Therefore, System 2 has solutions.
### System 3
[tex]\[ \begin{aligned} 2x + y &= 15 \quad \text{(1)} \\ x &= 15 - 2y \quad \text{(2)} \end{aligned} \][/tex]
Rewrite equation (2) in a different form:
[tex]\[ x + 2y = 15 \][/tex]
We now see that both equations are actually the same:
[tex]\[ 2x + y = 15 \][/tex]
Since both equations describe the same line, the system has infinitely many solutions. Therefore, System 3 has solutions.
### System 4
[tex]\[ \begin{aligned} 2x + y &= 17 \quad \text{(1)} \\ -4x &= 2y - 34 \quad \text{(2)} \end{aligned} \][/tex]
Rewrite equation (2) in standard form:
[tex]\[ -4x - 2y = -34 \][/tex]
Divide the entire equation by -2:
[tex]\[ 2x + y = 17 \][/tex]
We now have:
[tex]\[ 2x + y = 17 \][/tex]
Both equations are identical, meaning the system has infinitely many solutions. Therefore, System 4 has solutions.
### System 5
[tex]\[ \begin{aligned} 3y &= 10 - x \quad \text{(1)} \\ 2x + 6y &= 7 \quad \text{(2)} \end{aligned} \][/tex]
Rewrite equation (1) to standard form:
[tex]\[ x + 3y = 10 \implies x = 10 - 3y \][/tex]
Substitute [tex]\(x = 10 - 3y\)[/tex] in equation (2):
[tex]\[ 2(10 - 3y) + 6y = 7 \implies 20 - 6y + 6y = 7 \implies 20 = 7 \][/tex]
This is a contradiction. The system has no solution. Therefore, System 5 has no solution.
### System 6
[tex]\[ \begin{aligned} y &= 13 - 2x \quad \text{(1)} \\ 4x - y &= -1 \quad \text{(2)} \end{aligned} \][/tex]
Substitute [tex]\(y = 13 - 2x\)[/tex] into equation (2):
[tex]\[ 4x - (13 - 2x) = -1 \implies 4x - 13 + 2x = -1 \implies 6x - 13 = -1 \implies 6x = 12 \implies x = 2 \][/tex]
Substitute [tex]\(x = 2\)[/tex] into [tex]\(y = 13 - 2x\)[/tex]:
[tex]\[ y = 13 - 2(2) = 13 - 4 = 9 \][/tex]
The solution [tex]\( (x, y) = (2, 9) \)[/tex] satisfies both equations. Therefore, System 6 has a solution.
### Conclusion
The systems of equations with no solutions are:
- System 1
- System 5
### System 1
[tex]\[ \begin{aligned} x + 4y &= 23 \quad \text{(1)} \\ -3x &= 12y + 1 \quad \text{(2)} \end{aligned} \][/tex]
First, rewrite equation (2) to make it similar to equation (1):
[tex]\[ -3x - 12y = 1 \][/tex]
Now, let's put both equations in standard form:
[tex]\[ \begin{aligned} x + 4y &= 23 \\ -3x - 12y &= 1 \end{aligned} \][/tex]
Multiply equation (1) by 3:
[tex]\[ 3(x + 4y) = 3 \cdot 23 \implies 3x + 12y = 69 \][/tex]
Now we have:
[tex]\[ \begin{aligned} 3x + 12y &= 69 \\ -3x - 12y &= 1 \end{aligned} \][/tex]
Add these two equations:
[tex]\[ (3x - 3x) + (12y - 12y) = 69 + 1 \implies 0 = 70 \][/tex]
This is a contradiction. Therefore, System 1 has no solution.
### System 2
[tex]\[ \begin{aligned} 2x + 4y &= 22 \quad \text{(1)} \\ -x &= 2y - 11 \quad \text{(2)} \end{aligned} \][/tex]
Rewrite equation (2) to standard form:
[tex]\[ -x - 2y = -11 \][/tex]
Now, put the equations together:
[tex]\[ \begin{aligned} 2x + 4y &= 22 \\ -x - 2y = -11 \end{aligned} \][/tex]
Multiply equation (2) by 2:
[tex]\[ -2x - 4y = -22 \][/tex]
Now we have:
[tex]\[ \begin{aligned} 2x + 4y &= 22 \\ -2x - 4y &= -22 \end{aligned} \][/tex]
Add these two equations:
[tex]\[ (2x - 2x) + (4y - 4y) = 22 - 22 \implies 0 = 0 \][/tex]
This is an identity, meaning the system has infinitely many solutions. Therefore, System 2 has solutions.
### System 3
[tex]\[ \begin{aligned} 2x + y &= 15 \quad \text{(1)} \\ x &= 15 - 2y \quad \text{(2)} \end{aligned} \][/tex]
Rewrite equation (2) in a different form:
[tex]\[ x + 2y = 15 \][/tex]
We now see that both equations are actually the same:
[tex]\[ 2x + y = 15 \][/tex]
Since both equations describe the same line, the system has infinitely many solutions. Therefore, System 3 has solutions.
### System 4
[tex]\[ \begin{aligned} 2x + y &= 17 \quad \text{(1)} \\ -4x &= 2y - 34 \quad \text{(2)} \end{aligned} \][/tex]
Rewrite equation (2) in standard form:
[tex]\[ -4x - 2y = -34 \][/tex]
Divide the entire equation by -2:
[tex]\[ 2x + y = 17 \][/tex]
We now have:
[tex]\[ 2x + y = 17 \][/tex]
Both equations are identical, meaning the system has infinitely many solutions. Therefore, System 4 has solutions.
### System 5
[tex]\[ \begin{aligned} 3y &= 10 - x \quad \text{(1)} \\ 2x + 6y &= 7 \quad \text{(2)} \end{aligned} \][/tex]
Rewrite equation (1) to standard form:
[tex]\[ x + 3y = 10 \implies x = 10 - 3y \][/tex]
Substitute [tex]\(x = 10 - 3y\)[/tex] in equation (2):
[tex]\[ 2(10 - 3y) + 6y = 7 \implies 20 - 6y + 6y = 7 \implies 20 = 7 \][/tex]
This is a contradiction. The system has no solution. Therefore, System 5 has no solution.
### System 6
[tex]\[ \begin{aligned} y &= 13 - 2x \quad \text{(1)} \\ 4x - y &= -1 \quad \text{(2)} \end{aligned} \][/tex]
Substitute [tex]\(y = 13 - 2x\)[/tex] into equation (2):
[tex]\[ 4x - (13 - 2x) = -1 \implies 4x - 13 + 2x = -1 \implies 6x - 13 = -1 \implies 6x = 12 \implies x = 2 \][/tex]
Substitute [tex]\(x = 2\)[/tex] into [tex]\(y = 13 - 2x\)[/tex]:
[tex]\[ y = 13 - 2(2) = 13 - 4 = 9 \][/tex]
The solution [tex]\( (x, y) = (2, 9) \)[/tex] satisfies both equations. Therefore, System 6 has a solution.
### Conclusion
The systems of equations with no solutions are:
- System 1
- System 5
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.